Intraoperative 3D imaging in the treatment of elbow fractures - a retrospective analysis of indications, intraoperative revision rates, and implications in 36 cases. Issue 1 (December 2016) - Schnetzke, Marc; Fuchs, Julia; Vetter, Sven; Beisemann, Nils; Keil, Holger; Grützner, Paul-Alfred; Franke, Jochen
Abstract Background Three-dimensional (3D) imaging with a mobile C-arm has proven to be a valuable intraoperative tool in trauma surgery. However, little data is available concerning its use in the treatment of elbow fractures. The aim of the current study was to determine the intraoperative findings and consequences of 3D imaging in the treatment of elbow fractures. Methods Between 2001 and 2015, prospectively collected data of 36 patients who underwent intraoperative 3D imaging during elbow surgery were recorded. The findings and consequences of the intraoperative 3D scans were analyzed in a retrospective chart review. For clinical evaluation the analysis included the patients' medical history, the injury pattern of the affected elbow and concomitant injuries. Intraoperative and postoperative complications and revision surgeries were evaluated as well. Results In 6 patients (16.7 %) analysis of the intraoperative 3D scan led to an immediate revision due to the detection of intra-articular screw placement (n = 3, 8.3 %) and remaining intra-articular step of >2 mm (n = 3, 8.3 %). In all of these patients, correct implant positioning and anatomical reduction could be achieved after immediate intraoperative revision, which was verified by a repeated intraoperative 3D scan. None of the 36 patients needed surgical revision based on postoperative radiological examinations due to secondary dislocation, wrong implant placement or remaining steps in the articular surface. Conclusions Intraoperative 3D imaging offers additional information about fracture reduction and implant positioning in the treatment of elbow fractures compared to conventional intraoperative 2D imaging. It may therefore reduce the need for revision surgery. The value of intraoperative 3D imaging for clinical outcomes still needs to be assessed.